Comparative study of the effects of some NSAIDs on ovulation in female mice. - Al-Atrakji, Mohammed Q. Y.; Al-Zohyri, Ahmad M.; Al-Janabi, Adnan S. (Journal of the Faculty of Medicine Baghdad, 2012)
Background:Ovulation constitutes a central event in ovarian physiology, and ovulatory dysfunction which is a relevant cause of female infertility. Mammalian ovulation is comparable to aninflammatory reaction since many of the molecules responsible for inducing the inflammatorycascade including PGs, leukotrienes and various cytokines have been describedin the ovary. Objectives:This study was designed to compare between the effects of some NSAIDs(aspirin,diclofenac sodium and meloxicam)on the ovulatory process and the reproductive tract of female mice. Materials and methods:Twenty four female mice were subdivided into 4groups (6 animals/group).The first received distilled water serve as control group, the second receivedaspirin (7.5 mg/kg.B.W) ,thethird received diclofenac sodium(2mg/kg.B.W) and the fourth received meloxicam(0.001mg/kg.B.W) subcutaneously at proestrous phase,Blood was collected at metestrousfor subsequent hormonal assay. The whole reproductive tract was excised out, examined, weighed and ova were flushed. Results :Female mice that received 7.5 mg/kg.B.W of aspirin,showedenlarged, congested ovaries with cystic appearance and congested uteri with prominent blood vessels.Mice that received 2mg /kg.B.W.diclofenac and those received 0.01 mg/kg.B.W. meloxicam showed more congestion and more obvious cystic appearance of ovaries with uteri more bulky compared to controls that showed no congestion and no cystic appearance of the ovaries with thin non congested uteri.Highly significant (P < 0.001) increase in the ovarian weight and highly significant decrease in number of ova flushedwhile no significant changes (P > 0.05) were seen in the uterine weight nor in hormonal levels of LH and FSH between controls and each of animals that received aspirin, diclofenac and meloxicam respectively. Conclusion:Short -term administration of low-dose (aspirin, diclofenac& meloxicam) to female mice at proestrous cause a highly significant increase in the ovarian weight with morphological changes of ovaries and uteri and a highly significant decrease in the ovulatory rate as compared to controls .Greater effect were produced by meloxicam with a lower dose compare to diclofenac and aspirin.